E-Commerce Berbasis Marketplace Dalam Mempersingkat Penjualan Hasil Pertanian - Ivan Rinaldo; ulfa fitriyani yapan (Universitas Mitra Indonesia, 2023)
The agricultural sector has an important role in supporting the Indonesian economy. But on the other hand,sometimes many community groups do not benefit due to problems that arise because the distribution chain ofagricultural products are long enough, especially for farmers and consumers (end users). Of course the situationmust be improved, so that the agricultural products of Indonesia can be enjoyed by consumers or farmers withproper.Oneof its effortsisby establishing an e-Commercebasede-Commercesystem in agriculture.E-Commerce based e-Commerce system can be used as an alternative for farmers, used as a media campaign,communication and information and can cut the distribution chain of agricultural products marketing. Thebenefits felt by farmers and consumers directly and indirectly give a positive influence, especially from thebroadermarketingchannelsofagriculturalproductscanincreaseproductiondemandandspurtheprocurementof production among farmers and also the price offered to consumers will be cheaper so that sales in agriculturalproductscanbemore increasedandprofitablefor farmers.